Optimizing the addition of calcium carbonate (CaCo3) on the growth and survival of glass eel (Anguilla sp.) - Risna Sri Rahayu; Arif Supendi; Novita MZ (JURNAL MINA SAINS, 2023)
The development of eel fish cultivation has quite good business opportunities and prospects. However, the main obstacle in cultivating eel fish is the high mortality in the glass eel phase, so it has a survival rate of 30-50% and slow growth, namely less than 3.1%. One effort to maximize glass eel maintenance is through optimizing alkalinity as a buffer for water quality. The alkalinity level in the maintenance medium can be regulated by adding calcium carbonate (CaCO3). This research aims to determine the effect of adding CaCO3 to the rearing media on glass eels' growth and survival rate. The study was conducted for 14 days in March 2023. The method was wholly randomized with three replications in 3 treatments (P1=0 mg L-1, P2=50 mg L-1, P3=100 mg L-1). Analysis of research data used the ANOVA test. Adding CaCO3 produced a natural effect on length growth with a value of 0.16 cm, weight growth of 0.73 mg L-1, and a survival rate of 74%. The treatment did not naturally affect the alkalinity levels in the glass eel maintenance media. The best treatment effect was found in P2 (50 mg L-1). These results show that adding CaCO3 to the glass eel-rearing media decreased but did not naturally affect alkalinity levels.